The state of the art : a chronicle of American poetry, 1988-2014 - Lehman, David, 1948- (University of Pittsburgh Press, 2015)
"This book collects all twenty-nine forewords from The Best American Poetry series. Beginning with a new introduction by David Lehman and a foreword by poet Denise Duhamel (guest editor for The Best American Poetry 2013), the collection conveys a sense of American poetry in the making, year by year, over the course of a quarter of a century"-- Provided by publisher
Keywords: Poetics.; American poetry -- 21st century -- History and criticism.; American poetry -- 20th century -- History and criticism.; Poétique.; Poésie américaine -- 20e siècle -- Histoire et critique.; POETRY -- American -- General.; LITERARY CRITICISM -- Poetry.; American poetry; Poetics; 1900-2099; Criticism, interpretation, etc.